Universal Archive and Human Rights: a Visual Study on the Dialect of the Gaze - Gómez Moya, Cristián (2011)
In bringing up to date the meaning of the human right to be familiar with historical events involving political violence, resituated in the disjunctive that governs the modern preservation of traumatic memory –between the collection of documentary evidence and the ghost-like nature of data bases in cyberspace– the purpose of this article is to explore a debate around archive policies. Open policies by new digital media and the topological crisis that the euphoria sparked by universal access in detriment to local memories. Our disciplinary focus involves visual studies in relation to the circulation of biopolitical archives, which allows us to construct a dialect of the gaze on the Universal Archive category and the Human Rights tradition, whose accent is found in the multiplication of declassified documents and their global liberation through digital reproductions.